Muon Tomography Applied to a Dense Uranium Deposit at the McArthur River Mine. Issue 10 (29th October 2018) - Schouten, Douglas; Ledru, Patrick
Abstract: This article reports on the first application of muon tomography (a novel method for imaging density contrasts underground using cosmic rays) for imaging dense uranium deposits within the Athabasca Basin in Canada. We present a qualitative assessment of the radiographic imaging and 3‐D density inversion of a uranium deposit using muon tomography. The muon tomography survey summarized in this article was performed at the McArthur River mine. We demonstrate the validity of muon tomographic imaging with data acquired at a depth of about 600 m underground. The statistical significance of the uranium deposit signature in the muon data was larger than 5 standard deviations, and the corresponding 3‐D density inversion compared well with drill assay data from the deposit. Key Points: Muon tomography can be used for imaging density contrasts deep underground Muon tomography imaging is applicable to exploration of compact uranium deposits Three‐dimensional inversion for density from muon tomography data corresponds well to the density profile extracted from drill assay data